O fogo quebra a dormência e aumenta a germinação de espécies de cerrado? - Zirondi, Heloiza Lourenço [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Fire is one of the most important factors affecting plant communities in Brazilian tropical savannas (Cerrado), but less is understood about the regeneration strategies and fire-related germination cues. Thus, this study aimed to evaluate the effects of fire on the breaking of dormancy and stimulating germination of seeds of Fabaceae (hard-seeded coat and physically dormant) and Melastomataceae (soft-seeded coat and physiologically dormant). We hypothesized that seeds of Fabaceae (Mimosa pteridifolia Benth and Harpalyce brasiliana Benth.) would have their dormancy broken after the exposure to high temperatures, while the seeds of Melastomataceae (Comolia sertularia and Tibouchina cardinalis) would have their germination enhanced after the smoke treatments. Therefore, we exposed seeds (5 replicates/20 seeds/species) to different heat shock treatments (60°, 100°and 200°C) during 1' of exposition. We also prepared smoke solutions and soaked seeds (5 replicates/20 seeds/species) for 24hs into solutions 1:1 concentration. Seeds of control for heat shock were not exposed to high temperatures and for smoke experiments they were soaked in distilled water for 24 hs. After the treatments, the seeds were germinated in a growth chamber (27 ° C, 12/12 hours light) for 60 days. Germination was observed every three days. To see if there were statistically significant differences between treatments were performed variance analyzes of one (temperature, smoke) and two factors (temperature and smoke), applied to randomization tests (Euclidean distance between sampling units, 10,000 iterations). The results showed that only Harpalyce brasiliana had the dormancy broken by high temperatures, but all species studied were shown to be resistant to the passage of fire, with a decrease on germination percentage at 100 ° C. Regarding the smoke solution either species had its germination increased by the same. These are relevant information for a greater...

O fogo é um processo natural integrado nas funções de diversos ecossistemas. Ele é um importante fator ecológico no Cerrado, responsável por alterações na dinâmica, estrutura e composição das comunidades vegetais. Assim sendo, o fogo influencia processos importantes das comunidades, como a germinação, rebrote e o estabelecimento das plantas, sendo portanto, importante entender os seus efeitos nas respostas da vegetação. O estudo avaliou o efeito do fogo na germinação de sementes de duas espécies de Fabaceae (Mimosa pteridifolia Benth e Harpalyce brasiliana Benth., sementes impermeáveis) e duas espécies de Melastomataceae (Tibouchina cardinalis (Bonpl.) Cogn. e Comolia sertularia Triana; sementes permeáveis) de campo sujo e campo rupestre. Tem-se como hipótese principal que as sementes impermeáveis teriam suas dormências quebradas após exposição a altas temperaturas, enquanto que as sementes com tegumento permeável seriam estimuladas após a exposição a fumaça. Para testar a hipótese do trabalho foram realizados os seguintes tratamentos: exposição a altas temperaturas (durante 1') - 60°, 100° e 200ºC e uso de soluções líquidas de fumaça na concentração 1:1 (embebidas por 24 hs). Cada tratamento foi formado por 5 réplicas (com 20 sementes/réplica para cada espécie). Adicionalmente aos tratamentos já mencionados, dois controles foram utilizados: sem exposição a temperatura e embebidos em água destilada por 24 hs. Depois dos tratamentos, as sementes foram colocadas para germinar em câmaras de germinação (27ºC, 12/12 hs luz) durante 60 dias. A germinação foi observada a cada três dias. Para se verificar se houve diferença estatística entre os tratamentos foram realizadas análises de variância de um (temperatura, fumaça) e dois fatores (temperatura e fumaça), aplicados a testes de aleatorização (distância Euclidiana entre unidades amostrais, 10000 iterações). Os resultados mostraram...
Keywords: Cerrados; Germinação; Fogo; Melastomatacea; Sementes - Viabilidade